Herpetological Collections in the Thailand Natural History Museum as a Valuable Resource for Conservation and Education - Pattarapon Promnun; Kanokporn Panpong; Amonpong Khlaipet; Veera Vilasri; Jenjit Khudamrongsawat (Diversity, 2023)
The history of collecting and cataloging Thailand’s diverse herpetofauna is long-standing, with many specimens housed at the Thailand Natural History Museum (THNHM). This work aimed to assess the diversity of herpetofauna within the THNHM collection, ascertain conservation status of species, and track the geographical coverage of these specimens within the country. The THNHM collection boasts an impressive inventory, numbering 173 amphibian species and 335 reptile species. This collection reflects the substantial biodiversity within these taxonomic groups, rivaling the total number of herpetofauna species ever recorded in Thailand. However, the evaluation of their conservation status, as determined by the IUCN Red List, CITES, and Thailand’s Wild Animal Preservation and Protection Act (WARPA), has unveiled disparities in the degree of concern for certain species, possibly attributable to differential uses of the assessment criteria. Notably, the museum houses a number of type specimens, including 27 holotypes, which remain understudied. Sampling efforts have grown considerably since the year 2000, encompassing nearly all regions of the country. This extensive and systematic collection of diverse herpetofauna at the THNHM serves as a valuable resource for both research and educational purposes, enriching our understanding of these species and their significance in the broader context of biodiversity conservation.